A comparative study of age-related hearing loss in wild type and insulin-like growth factor I deficient mice - Riquelme, Raquel; Cediel, Rafael; Contreras, Julio; Rodríguez-de La Rosa, Lourdes; Murillo-Cuesta, Silvia; Hernandez, Catalina; Zubeldia, Jose M.; Cerdan, Sebastian; Varela-Nieto, Isabel (Frontiers in Neuroanatomy, 2010)
Insulin-like growth factor-I (IGF-I) belongs to the family of insulin-related peptides that fulfils a key role during the late development of the nervous system. Human IGF1 mutations cause profound deafness, poor growth and mental retardation. Accordingly, Igf1−/− null mice are dwarfs that have low survival rates, cochlear alterations and severe sensorineural deafness. Presbycusis (age-related hearing loss) is a common disorder associated with aging that causes social and cognitive problems. Aging is also associated with a decrease in circulating IGF-I levels and this reduction has been related to cognitive and brain alterations, although there is no information as yet regarding the relationship between presbycusis and IGF-I biodisponibility. Here we present a longitudinal study of wild type Igf1+/+ and null Igf1−/− mice from 2 to 12 months of age comparing the temporal progression of several parameters: hearing, brain morphology, cochlear cytoarchitecture, insulin-related factors and IGF gene expression and IGF-I serum levels. Complementary invasive and non-invasive techniques were used, including auditory brainstem-evoked response (ABR) recordings and in vivo MRI brain imaging. Igf1−/− null mice presented profound deafness at all the ages studied, without any obvious worsening of hearing parameters with aging. Igf1+/+ wild type mice suffered significant age-related hearing loss, their auditory thresholds and peak I latencies augmenting as they aged, in parallel with a decrease in the circulating levels of IGF-I. Accordingly, there was an age-related spiral ganglion degeneration in wild type mice that was not evident in the Igf1 null mice. However, the Igf1−/− null mice in turn developed a prematurely aged stria vascularis reminiscent of the diabetic strial phenotype. Our data indicate that IGF-I is required for the correct development and maintenance of hearing, supporting the idea that IGF-I-based therapies could contribute to prevent or ameliorate age-related hearing loss.